2001
DOI: 10.1242/jeb.204.24.4345
|View full text |Cite
|
Sign up to set email alerts
|

Venom flow in rattlesnakes: mechanics and metering

Abstract: SUMMARY The functional morphology of venom injection in Crotalus atrox was explored using high-speed digital videography combined with direct recording of venom flow using perivascular flow probes. Although venom flow was variable, in most strikes the onset of venom flow was coincidental with fang penetration, and retrograde flow (venom suction) was observed prior to fang withdrawal. The duration of venom flow was consistently less than the duration of fang penetration. The occurrence of retrogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…However, in contrast to some other studies, snakebites without envenomation ("dry" bites) were very rare. Russell found that 18% to 22% of bites were dry, 7 and Young and Zahn found that 35% of bites were dry, 20 while Tanen et al, like us, documented a low incidence of dry bites (3%). 18 The differences among studies may be due to different ways of judging snakebite severity.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…However, in contrast to some other studies, snakebites without envenomation ("dry" bites) were very rare. Russell found that 18% to 22% of bites were dry, 7 and Young and Zahn found that 35% of bites were dry, 20 while Tanen et al, like us, documented a low incidence of dry bites (3%). 18 The differences among studies may be due to different ways of judging snakebite severity.…”
Section: Discussionmentioning
confidence: 55%
“…7 There are data showing that rattlesnakes are able to meter their venom such that smaller prey may receive less venom than larger prey, 19 and one could speculate that children, although they are not prey, may receive less venom than adult patients. On the other hand, there are also data showing that venom flow in defensive strikes does not differ with different target sizes, 20 although arguably the mechanics of venom flow are not necessarily predictive of total venom delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…75,76 (Not recommended) THE DRY BITE Venomous snakes may also fail to deliver venom in an event commonly referred to as a dry bite that may occur in 25% or more of crotaline bites. 25,77 Duration of fang contact also affects the amount of venom injected in both predatory and defensive situations, with venom quantities from defensive bites (eg, to humans) being more Even a knowledgeable caregiver may not be able to predict the amount of envenomation from a snakebite or potential sequelae, and therefore observation for the sake of risk stratification is not recommended. [Recommendation grade: 2C] Every effort should be made to evacuate snakebite patients; however, if the patient is in a remote location with a difficult evacuation, further considerations must be weighed, including patient and rescuer safety, likelihood of successful evacuation, and availability of resources required to carry out the evacuation.…”
Section: Pressure Bandagingmentioning
confidence: 99%